2015
DOI: 10.1166/jnn.2015.10834
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Hyaluronan Conjugated Super-Paramagnetic Iron Oxide Nanoparticles (DOX-HA-SPION) Enhanced Cytoplasmic Uptake of Doxorubicin and Modulated Apoptosis, IL-6 Release and NF-kappaB Activity in Human MDA-MB-231 Breast Cancer Cells

Abstract: Triple negative breast cancer exhibit increased IL-6 expression compared with matched healthy breast tissue and a strong link between inflammation and cancer progression and metastasis has been reported. We investigated whether doxorubicin-hyaluronan-super-paramagnetic iron oxide nanoparticles (DOX-HA-SPION) would show greater therapeutic efficacy in human triple negative breast cancer cells (TNBC) MDA-MB-231, as was recently shown in drug-sensitive and multidrug-resistant ovarian cancer cells. Therefore, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…7A). Previous studies using DOX-conjugated nanoparticles have shown that the cytotoxic effect of DOX is preserved and capable of inducing both apoptosis and necrosis in different cell lines [43][44][45][46] . On the other hand, other studies have explained that QDs-based distribution of DOX enabled cell expansion and as a consequence, yielded better pharmacological results [44] .…”
Section: Resultsmentioning
confidence: 99%
“…7A). Previous studies using DOX-conjugated nanoparticles have shown that the cytotoxic effect of DOX is preserved and capable of inducing both apoptosis and necrosis in different cell lines [43][44][45][46] . On the other hand, other studies have explained that QDs-based distribution of DOX enabled cell expansion and as a consequence, yielded better pharmacological results [44] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also demonstrate that chemotherapy drug effects on adipose tissue may be mediated by DOX-induced activation of NFÎșB and inflammatory cytokines [ 18 , 19 ]. Studies on rodent models demonstrated that DOX increases serum total cholesterol, triglyceride and LDL levels when compared to controls [ 20-22 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPIONs have higher magnetic properties than paramagnetic materials due to their ability to spin alignment to an external magnetic field SPIONs can generate heat inside the tumors producing apoptosis by using hyperthermia as well as real time images into the tumors [195] Experimental/clinicalongoing SPIONs are often use in human triple-negative breast cancer cells (TNBC) MDA-MB-231 therapeutics [209]. Table 2.…”
Section: Spions (Superparamagnetic Iron Oxide Nanoparticles)mentioning
confidence: 99%